ANALISIS KUALITAS PELAYANAN INTERNET INDIHOME PADA PT. X DENGAN PENDEKATAN PART LEAST SQUARE - Kukuh Winarso; Moh. Jufriyanto (Matrik : Jurnal Manajemen dan Teknik Industri Produksi, 2019)
PT. X Provides paid internet services known as Indihome. The problem that occurs in Indihome Internet service is that there are 42.36% complaints from consumers to the service process provided by PT. X and there is a 7.46% complaint about the amount of the bill. The purpose of this study is to model and know what variables affect the quality of the Indihome Internet service. The method used is Partial Least Square (PLS). Partial Least Square (PLS) is one of the multivariate statistical analysis techniques that can handle multiple response variables and an explanatory variable. The variables used are tangible, empathy, assurance, reliability and responsiveness. The results of the research are the increase of R square value after the implementation of the A5 indicator that does not meet the model PLS. All five variables affect the quality of indihome Internet service is 76,1%. Based on the hypothesis test results on the outer model It is said that the variable indicator is valid with p-value = 0 < 0,05. In testing the inner model obtained that the variable tangible and responsiveness has no significant effect on the quality of Internet service Indihome, while the variable empathy, assurance, reliability significantly affect the quality of service Indihome Internet.